Answer :

Let his present age be x

4 years ago his age = x-4 years


After 12 years his age = 12 + x years


According to the question


12 + x = 3(x-4)


12 + x = 3x-12


x-3x = -12-12


-2x = -24


x = 12


(divide by -2 on both the sides)


The present age of the person = 12 years


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-GBNCERT - Mathematics Exemplar

<span lang="EN-GBNCERT - Mathematics Exemplar

<span lang="EN-GBNCERT - Mathematics Exemplar

<span lang="EN-GBNCERT - Mathematics Exemplar

<span lang="EN-GBNCERT - Mathematics Exemplar

<span lang=NCERT - Mathematics Exemplar

<span lang=NCERT - Mathematics Exemplar

If numeratoNCERT - Mathematics Exemplar